Synthesis of Benzoisoxazole Derivatives and Evaluation of Inhibitory Potency against Cholinesterase for Alzheimer's Disease Therapeutics. (29th August 2016) - Park, Jung‐Youl; Shin, Sujeong; Kim, Jae‐kwan; Park, Kyoung Chan; Park, Jeong Ho
Abstract : To improve Alzheimer's disease (AD) therapeutics, we have designed and synthesized new benzoisoxazole derivatives that are potent inhibitors of cholinesterase (acetylcholinesterase [AChE] and butyrylcholinesterase [BuChE]). Since inhibition of cholinesterase (ChE) is still considered to be one of the most effective ways of treating AD patients, many new classes of ChE inhibitors have been synthesized. To identify a new type of cholinergic drug, the benzoisoxazole moiety which is the pharmacophore moiety of Risperidone was coupled with natural antioxidants. Some benzoisoxazole derivatives (26–28 and30 ) were found to effectively inhibit BuChE (IC50 < 20 μM), and some (20 and26–28 ) to moderately inhibit AChE (IC50 < 100 μM). Furthermore, compound28 showed better inhibitory activity against BuChE (IC50 = 0.72 ± 0.11 μM) than galantamine (IC50 = 8.4 ± 0.1 μM). The new benzoisoxazole derivatives showing BuChE inhibitory activity represent a new class of ChE inhibitor and can be used to create novel compound derivative drugs for treating AD patients. Abstract :